Mechanical Properties Of Polymer Modified Ferrocement - Sharma, Pardeep (My University, 2013)
In an effort to improve the performance of mortar, polymer is introduced into mortar. It has been reported that polymer-modified mortar (PMM) is more durable than conventional mortar due to higher strength. This research was carried out to establish the effects of polymer addition on compressive strength, flexural strength, modulus of elasticity of mortar and flexural strength and tensile strength values on polymer modified ferrocement samples with mortar of constant flow value. Two types of polymers were used i.e SBR and VAE polymer. The mixes were prepared with polymer-cement ratio of 0% , 5%, 10%, 15% and 20% for each and a flow value of 110 +_ 5 is fixed for every mix of mortar. The addition of polymer in the mortar results in reduction of w/c ratio for the mixes with constant flow value while mixes with same w/c ratio result in increase in flow value. The results indicated that the compressive strength of polymer modified mortar is lower than the unmodified mortar for constant w/c ratio after 7 and 28 days of wet curing days. The compressive strength of SBR polymer modified mortar increases but of VAE modified mortar decreases after 7 and 28 days at varied w/c ratio. The flexure strength increases for both mixes of the varried w/c ratio at the same flow value. The main aim of polymer addition is to increase the flexure or bending stress of conventional mortar. The modulus of elasticity of conventional mortar is higher than that of polymer modified mortar and the failure of conventional mortar was found more brittle and less deflection value as compared to the polymer modified mortar. The flexure strength of ferrocement samples also increases on polymer addition for third point loading test. Polymer modification of cement paste increases its tensile and flexural strength and reduces its brittle nature. We will conclude by showing that future use of polymer modified cement composites will likely be in the area of durability and performance improvements of cement materials applied in thin sections.
ME, CED
Keywords: POLYMER; MORTAR; FLEXURE; SPLIT TENSILE; COMPRESSIVE STRENGTH